Detecting falls at home: User-centered design of a pervasive technology - Cuvillier, Bruno; Chaumon, Marc; Body, Salima; Cros, Florence (Human Technology, 2016)
Falling is the main cause of domestic accidents and fatal injuries to seniors at home. In this paper, we describe the design process for a new pervasive technology (CIRDO). The aim of this technology is to detect falls (via audio and video sensors) and to alert the elderly’s family or caregivers. Two complementary studies were performed. Firstly, the actual risk situations of older adults were analyzed. Secondly, social acceptance was investigated for the different homecare field stakeholders. Our results highlight the tensions among social actors towards the tool and their impacts on technology acceptance by the elderly. Also, we show a significant change in the fall process due to the device. In actuality, the social functions associated with CIRDO implementation and the necessity of iterative design processes suggest that the CIRDO system should be more flexible and versatile to better fit the risk behaviors of seniors that evolve using this device.